hNIS-based imaging to monitor treatment with the novel oncolytic virus CF33-hNIS-antiPDL1 in humans with advanced triple negative breast cancer - Rand, Jamie; Yamauchi, Dave; Chaurasiya, Shyambabu; Zhang, Jianying; Deshpande, Supriya; Chong, Leslie; Seiz, Amanda; Meisen, Hans; Fong, Yuman; Yuan, Yuan (Frontiers in Oncology, 2025)
BackgroundTriple-negative breast cancer (TNBC) is clinically aggressive. CF33-hNIS-antiPDL1, an oncolytic orthopoxvirus, shows robust anti-cancer activity in TNBC xenografts in mice. CF33-hNIS-antiPDL1-infected tumor cells express functional human sodium iodide symporter (hNIS) and are visible by single-photon emission computed tomography (SPECT) or positron emission tomography (PET). We evaluated the ability of virus-encoded hNIS to track OV in mice using PET imaging and in a phase I study in TNBC patients using SPECT. The aim of this first-in-human study was to determine imageability and safety of intratumoral (IT) CF33-hNIS-antiPDL1 injections.MethodsImageability of CF33-hNIS-antiPDL1 was first assessed in mice bearing human xenografts. Virus or PBS-treated mice were imaged using a PET scanner. For the first-in-human trial, 9 patients were enrolled in this phase I, single-center, single-arm trial from October 2021 to August 2023. Key eligibility criteria included unresectable/metastatic TNBC; progressed on at least 2 prior chemotherapies; ECOG 0-2; RECIST 1.1 measurable disease; and at least one tumor amenable to repeated IT injections. Eligible patients received CF33-hNIS-antiPDL1 IT at 1 of 6 assigned dose levels (ranging from 1 × 105 PFU to 3 x 108 PFU) on days 1 and 15 of each 28-day cycle for 3 treatment cycles. SPECT whole-body imaging was performed using technetium-99 at cycle 1 day 8.ResultsAll mice treated with the virus showed clear PET signal from tumors whereas no signal was observed in PBS-treated mice. In the phase I study, 7 of 9 patients (78%) showed uptake at the injection site on SPECT imaging at C1D8. Five of 5 patients (100%) with injection sites at metastatic subcutaneous nodules, intramuscular masses, or axillary lymph nodes, and 2/4 patients (50%) with injection sites at matted dermal metastatic lesions had uptake at injected lesions.ConclusionSPECT imaging successfully showed enhancement at the injected lesions in 78% of patients treated with CF33-hNIS-antiPDL1, even at low doses of the oncolytic virus (OV), suggesting local viral replication and hNIS expression. This is the first report of hNIS-based imaging to track oncolytic poxvirus replication in humans. This technology holds promise for noninvasive tracking of systemically administered OVs and other therapies.Clinical trial registrationhttps://www.clinicaltrials.gov/study/NCT05081492, identifier NCT05081492.